Differential Diagnosis of Psychotic Process in Adulthood Autistic Spectrum Disorders: Case Series - Ozen, Murat Eren; Kiliclioglul, Umit; Orum, Mehmet Hamdi; Kalenderoglu, Aysun; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2018)
Schizophrenia is a psychiatric disorder that usually begins at an early age when significant disturbances are seen in feelings, thoughts, and behaviors, where the patient is distracted from the facts and has problems in interpersonal relationships and social withdrawal. Autism is a neurodevelopmental disorder that prevents brain development, which causes limited and repetitive behaviors that damages social interaction and communication. Although the differences between schizophrenia and autism have been revealed at the theoretical level, especially in high-functioning autism, inability to be diagnosed at an early age, the similarity of symptoms has led to the confusion of these two disorder symptoms in later life. In adulthood, the bizarre speech in autism patients, strong and irrevocable beliefs, can be confused with disorganized speech and delusions in patients with schizophrenia. When differentiating between the two disorders, it is emphasized that the more commonly held thinking is based on a logical basis. In this study, three cases with differentiating diagnosis of autism and schizophrenia were reported.
Keywords: Schizophrenia; autism; Asperger's syndrome; adult autistic spectrum disorder; differential diagnosis